Pengaruh Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderating - Rival Rohmawan; Yeni Oktaviani; Pitri Yandri (IAIN Batusangkar, 2021)
This study aims to test the effect of CSR on firm value (stock price) with profitability as a moderating variable with quantitative approach on the 7 manufacturing companies listed in Indonesia stock Exchange (BEI) in the period from 2013 to 2019, so there are 49 observational data acquired. The sampling method using purposive sampling with the criteria that have been determined. Data analysis method used is the analysis of panel data regression with the aid of EViews 10. The results showed that CSR does not affect the Profitability of the proxies ROA can not strengthen the influence of CSR on stock price. Simultaneously, CSR and profitability as a moderating effect on stock prices.